2018
DOI: 10.1111/jsap.12909
|View full text |Cite
|
Sign up to set email alerts
|

Position of maximal nasopharyngeal maximal occlusion in relation to hamuli pterygoidei: use of hamuli pterygoidei as landmarks for palatoplasty in brachycephalic airway obstruction syndrome surgical treatment

Abstract: The hamuli pterygoidei are a reliable landmark for soft palate incision for palatoplasty in these cases but the distance between them and the site of maximal nasopharyngeal occlusion varied greatly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…33,54 In addition, the most caudal aspect of the hard palate (level X) and the hamulae of the pterygoid (level Y) are consistent, readily identified, repeatable landmarks for both skull types that have been previously used as anatomic landmarks for soft palate measurements, providing easily repeatable measurements. 6,33 Cross-sectional areas were chosen because they are easier to measure in the software and more repeatable than volumes. All of the variables compared at these two levels verified that brachycephalic dogs have more soft tissue than air and more soft tissue in their airway compared with mesaticephalic dogs.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…33,54 In addition, the most caudal aspect of the hard palate (level X) and the hamulae of the pterygoid (level Y) are consistent, readily identified, repeatable landmarks for both skull types that have been previously used as anatomic landmarks for soft palate measurements, providing easily repeatable measurements. 6,33 Cross-sectional areas were chosen because they are easier to measure in the software and more repeatable than volumes. All of the variables compared at these two levels verified that brachycephalic dogs have more soft tissue than air and more soft tissue in their airway compared with mesaticephalic dogs.…”
Section: Discussionmentioning
confidence: 84%
“…Our rationale for choosing two specific levels to examine the cross‐sectional anatomy was based on preliminary assessments of brachycephalic head and neck CT and previous studies in which areas of known obstruction in brachycephalic dogs were shown . In addition, the most caudal aspect of the hard palate (level X) and the hamulae of the pterygoid (level Y) are consistent, readily identified, repeatable landmarks for both skull types that have been previously used as anatomic landmarks for soft palate measurements, providing easily repeatable measurements . Cross‐sectional areas were chosen because they are easier to measure in the software and more repeatable than volumes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Determining the optimal method of surgical management of these dogs is an area of active research, with several procedures currently in common use . The mortality risk in this group is relatively high at 3.2% to 7% .…”
Section: Introductionmentioning
confidence: 99%